A cross sectional study on quality of life of PLHIV and their psychosocial correlates at tertiary care hospital, Lucknow - Gautam, Anuradha; Mishra, Chandra Mauli (International Journal Of Community Medicine And Public Health, 2022)
Background: People living with HIV/AIDS (PLHIV) are prone to psychological illnesses. HIV/AIDS, not only affects physical health but also emotional and mental health, which affects quality of life (QoL). The aim of present study was to assess the psychosocial variables affecting QoL of PLHIV. Methods: A cross sectional study was done at ART plus centre of a tertiary care hospital of Lucknow, among PLHIV. The questionnaire contained details of the socio-demographic, clinical characteristics, QoL and psychosocial factors including stress, depression, anxiety, stigma, coping and self-transcendence. To see any significant correlation Pearson’s correlation was used to identify relationship between different domains of QoL and psychosocial factors associated with PLHIV. Logistic regression was also used to identify predictors of QoL by using SPSS version 23.0. Results: QoL was rated as poor by 12.2% of the study subjects and 14.6% were dissatisfied with their overall health status. QoL score was highest in “physical health” and “level of independence” domain and the minimum mean score was in “psychological” domain. All the domains of QoL were found to be positively correlated with ‘self-transcendence’ and negatively correlated with ‘stress, depression, anxiety and internalized stigma’. Conclusions: Self-transcendence act as a healing role to improve QoL while depression, stress and anxiety negatively associated with QoL.